Media Pembelajaran Aktivitas Pengembangan PJOK untuk Pendidikan Dasar dan Menengah - Made Agus Wijaya; I Nyoman Kanca (Fakultas Ilmu Olahraga, Universitas Negeri Surabaya, 2019)
The development of Physical Education/ PE learning media that can be accessed widely by students, shortening waiting times and increasing hours of active moving/ learning time is an urgent needed by primary and secondary education PE teachers in Buleleng-Bali Regency. This study aims to develop learning media PE fitness activities for primary and secondary education. This development research refers to the development model of Borg and Gall. This research was conducted in 5 elementary schools, 2 junior high schools and 2 high schools in Buleleng Regency, involving 219 students. The results of the study show that at the time of the small group trials, there were 95.76% (68 students) of the students who were positive about the motion cards for the fitness activities of the PE, thus at the time of the large group trials, 96.70% (151 students) had positive opinions. According to students, this motion card displays images, writing and motion tasks that are clear, easy and safe to carry, easy to hold and not heavy held by students. The conclusion of this study is that motion cards for PE fitness activities can be implemented in primary and secondary education.